Hitler à Hollywood - Medeiros, Maria de 1965-; Willaert, Wim 1967-; Presle, Micheline 1922-2024; Morel, François 1959-; Lonsdale, Michael 1931-2020; Baye, Nathalie 1948- (Eurozoom, 2011)
"A bio-doc about Micheline Presle changes into a thrilling investigation of the long hidden truth about European cinema. This mockumentary thriller uncovers Hollywood's unsuspected plot against the European motion picture industry. Numerous directors and stars appear in the film, making it a choice morsel for all film lovers." [amazon.de]
Original: Frankreich 2010
Bildformat 16:9
Bonus: entretiens ; portrait et tornage
Keywords: Presle, Micheline -- 1922-2024; DVD-Video